Small-Signal Stability and Resonance Perspectives in Microgrid: A Review - Awan Uji Krismanto; Nadarajah Mithulananthan; Rakibuzzaman Shah; Herlambang Setiadi; Md. Rabiul Islam (Energies, 2023)
The microgrid (MG) system is a controlled and supervised power system consisting of renewable energy (RE)-based distributed generation (DG) units, loads, and energy storage. The MG can be operated autonomously or while connected to the grid. Higher intermittencies and uncertainties can be observed in MGs compared to the conventional power system, which is the possible source of small-signal stability in MG systems. It can be seen as disturbances around the stable operating point, which potentially lead to the small-signal instability problem within MGs. Small-signal instability issues also emerge due to the lack of damping torque in the MG. The integration of power electronic devices and complex control algorithms within MGs introduces novel challenges in terms of small-signal stability and possible resonances. The occurrence of interaction in a low- or no-inertia system might worsen the stability margin, leading to undamped oscillatory instability. The interaction within the MG is characterized by various frequency ranges, from low-frequency subsynchronous oscillation to high-frequency ranges around the harmonic frequencies. This study presents an overview of the dynamic model, possible sources of small-signal instability problems, and resonance phenomena in MGs. The developed models of MG, including structure, converter-based power generation, and load and control algorithms, are briefly summarized to provide the context of MG system dynamics. A comprehensive critical review of the previous research, including small-signal stability and resonance phenomenon for MGs, is also provided. Finally, key future research areas are recommended.